Spicebush Swallowtail Papilio (Pterourus) troilus Linnaeus 1758 (Insecta: Lepidoptera: Papilionidae: Papilioninae) - Donald W. Hall; Jerry F. Butler (EDIS)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 11-page fact sheet that discusses the spicebush swallowtail butterfly was written by Donald W. Hall and Jerry F. Butler, and published by the UF Entomology and Nematology Department, November 2015.